Hospital response challenges and strategies during COVID-19 pandemic: a qualitative study - Mohammadinia, Leila; Saadatmand, Vahid; Khaledi Sardashti, Hassan; Darabi, Saeid; Esfandiary Bayat, Fahimeh; Rejeh, Nahid; Vaismoradi, Mojtaba (Frontiers in Public Health, 2023)
Background: At the beginning of the COVID-19 pandemic, healthcare managers at hospitals did not have sufficient experiences to appropriately respond to the COVID-19 outbreak. Due to a lack of preparedness, many challenges arose in the healthcare system, and each country developed and implemented strategies depending on national policies. This study aimed to understand challenges during the COVID-19 pandemic and strategies used in Iranian hospitals. Methods: A qualitative research was conducted in four hospitals in an urban area of Iran. In-depth Semi-structured interviews were performed with 32 participants including healthcare managers, nurses, and medical doctors. Data underwent qualitative content analysis. Results: Four categories were developed: ‘capacity expansion’, ‘management affairs’, ‘diagnostic services’’, and therapeutic services’. Each category consisted of 2-3 subcategories. Conclusion: Hospitals should be prepared to intelligently respond to future epidemics. It is necessary to develop a comprehensive epidemic plan for the management of disasters to reduce the impact of the epidemic and minimize the risk to public health and ensure that resources are allocated in an efficient and effective manner.